One-year Surgical Outcomes and Costs for Medicaid Versus Non-Medicaid Patients Undergoing Laparoscopic Roux-en-Y Gastric Bypass: A Single-Center Study. Issue 1 (February 2016) - Chen, Ellie Y.; Fox, Benjamin T.; Suzo, Andrew; Greenberg, Jacob A.; Campos, Guilherme M.; Garren, Michael J.; Funk, Luke M.
Abstract : Purpose: To compare 1-year outcomes and costs between severely obese Medicaid and non-Medicaid patients who underwent laparoscopic Roux-en-Y gastric bypass surgery. Methods: This is a single-institution retrospective review comparing 33 Medicaid patients to 99 randomly selected non-Medicaid patients (1:3 case-control). Ninety-day and 1-year outcomes were extracted from the electronic health record. Costs were obtained from the UW information technology division. Bivariate analyses were used to compare study variables. Results: Emergency department visits (48.2% vs. 27.4%; P =0.06) and readmissions (37.0% vs. 14.7%; P =0.01) were more common for Medicaid patients. Medicaid patients had less excess body weight loss (50.7% vs. 65.6%; P =0.001) but similar comorbidity resolution and complication rates. One-year median costs were similar between Medicaid and non-Medicaid patients (21, 160 vs. 24, 215; P =0.92). Conclusions: One-year comorbidity resolution, complications, and costs following laparoscopic Roux-en-Y gastric bypass were similar between Medicaid and non-Medicaid patients. Focusing on reducing emergency department presentations and readmissions would be a high-impact area for future quality improvement initiatives. Abstract : Supplemental Digital Content is available in the text.